Microplastic pollution promotes soil respiration: A global‐scale meta‐analysis - Shuling Zhao; Matthias C. Rillig; Haijian Bing; Qingliang Cui; Tianyi Qiu; Yongxing Cui; Josep Penuelas; Baiyan Liu; Shiqi Bian; Fazel Abdolahpur Monikh; Jing Chen; Linchuan Fang (Global Change Biology, 2024)
Microplastic (MP) pollution likely affects global soil carbon (C) dynamics, yet it remains uncertain how and to what extent MP influences soil respiration. Here, we report on a global meta‐analysis to determine the effects of MP pollution on the soil microbiome and CO 2 emission. We found that MP pollution significantly increased the contents of soil organic C (SOC) (21%) and dissolved organic C (DOC) (12%), the activity of fluorescein diacetate hydrolase (FDAse) (10%), and microbial biomass (17%), but led to a decrease in microbial diversity (3%). In particular, increases in soil C components and microbial biomass further promote CO 2 emission (25%) from soil, but with a much higher effect of MPs on these emissions than on soil C components and microbial biomass. The effect could be attributed to the opposite effects of MPs on microbial biomass vs. diversity, as soil MP accumulation recruited some functionally important bacteria and provided additional C substrates for specific heterotrophic microorganisms, while inhibiting the growth of autotrophic taxa (e.g., Chloroflexi , Cyanobacteria ). This study reveals that MP pollution can increase soil CO 2 emission by causing shifts in the soil microbiome. These results underscore the potential importance of plastic pollution for terrestrial C fluxes, and thus climate feedbacks.